Marmoset Viral Hepatic Inflammation Induced by Hepatitis C Virus Core Protein via IL-32 - Liu, Bochao; Ma, Xiaorui; Wang, Qi; Luo, Shengxue; Zhang, Ling; Wang, Wenjing; Fu, Yongshui; Allain, Jean-Pierre; Li, Chengyao; Li, Tingting (Frontiers in Cellular and Infection Microbiology, 2020)
Common marmosets infected with hepatitis C virus (HCV)/GB virus-B (GBV-B) chimeras containing HCV core and envelope proteins (CE1E2p7) developed more severe hepatitis than those infected with HCV envelope proteins (E1E2p7), suggesting that HCV core protein might be involved in the pathogenesis of viral hepatitis. The potential role of HCV core in hepatic inflammation was investigated. Six individual cDNA libraries of liver tissues from HCV CE1E2p7 or E1E2p7 chimeras infected marmosets (3 animals per group) were constructed and sequenced. By differential expression gene (DEG) analysis, 30 of 632 mRNA transcripts were correlated with immune system process, which might play a role in hepatitis. A protein-protein interaction network was constituted by STRING database based on these 30 DEGs, showing that IL-32 might play a central regulatory role in HCV core-related hepatitis. To investigate the effect of HCV core protein on IL-32 expression, HCV core expressing and mock constructs were transfected into Huh7 cells. IL-32 mRNA and secretion protein were detected at significantly higher levels in cells expressing HCV core protein than in those without HCV core expression (P<0.01 and P<0.001, respectively). By KEGG enrichment analysis and using the specific signaling pathway inhibitor LY294002 for inhibition of PI3K, IL-32 expression was significantly reduced (P<0.001). In conclusion, HCV core protein induces an increase of IL-32 expression via PI3K pathway in hepatic cells, which played a major role in development of HCV-related severe hepatitis.